Has Monetary Policy Become More Effective? - Boivin, Jean; Giannoni, Marc P (The Review of Economics and Statistics, 2006)
We investigate the implications of changes in the structure of the U.S. economy for monetary policy effectiveness. Estimating a vector autoregression over the pre- and post-1980 periods, we provide evidence of a reduced effect of monetary policy shocks in the latter period. We estimate a structural model that replicates well the economy's response in both periods, and perform counterfactual experiments to determine the source of the change in the monetary transmission mechanism and in the economy's volatility. We find that by responding more strongly to inflation expectations, monetary policy has stabilized the economy more effectively in the post-1980 period.